Acetaminophen degradation by electro-fenton and photoelectro-fenton processes using a double cathode electrochemical cell - Veciana, Mersabel L. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
This study demonstrates th applicability of the electro-Fenton (EF) and photoelectron-Fenton (PEF) processes using a double cathode electrochemical cell in the treatment of acetaminophen (ACT) containing wastewater. EF and PEF rely on hydroxyl radical generation from Fenton's reagents for pollutant degradation. Synthetic ACT-containing wastewater was prepared using ultrapure water. Box-Behnken design was utilized to optimize and determine the effects of operating parameters such as: Fe²+ and H₂O₂ dosages and applied current density. These parameters positively affect the ACT degradation efficiency with the initial Fe²+ concentration being the most significant parameter for both processes. Optimum conditions for maximum ACT removal were 0.087 mM Fe²+, 16.26 mM H₂O₂ and 37.67 A/m² for the EF process and 0.08 mM Fe²+, 14.81 mM H₂O₂ and 37.67 A/m² for the process. At optimum conditions, ACT removal efficiencies of 97.93% and 96.97% and corresponding COD removals of 42.72% and 42.26% were obtained for EF and PEF methods, respectively. TOC removals of 18.99% and 20.07% for EF and PEF processes respectively were achieved after 120 minutes. Models obtained are applicable to a wide range of ACT concentrations and can be used in scale-ups. Thirteen types of intermediates were identified and a degradation pathway was proposed.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Acetaminophen; Sewage -- Purification -- Biological treatment; Electro-Fenton process; Fenton process